Esbjerg og dens Ud- og Indførsel, navnlig af Landbrugsprodukter fra 1874—92. - Hassing, Capt. (Tidsskrift for Landøkonomi, 2018)
Esbjerg og dens Ud- og Indførsel, navnlig af Landbrugsprodukter fra 1874—92.